The Morse oscillator generalised from supersymmetry - Drigo Filho, Elso [UNESP] (Iop Publishing Ltd, 1988)
Using the factorisation method in supersymmetric quantum mechanics the author determines new potentials from the Morse oscillator. This method is applied although the ladder operators are not used.